KONSEP MOTIVASI DALAM MEWUJUDKAN PRODUKTIVITAS KARYAWAN PADA PT NANBU PLASTICS INDONESIA - Ahmad Gunawan (Valid: Jurnal Ilmiah, 2019)
Productivity in an organization or company is basically centered on the human resources owned by the organization. Considering the importance of human resources, attention, direction, and regulation of human resources need to be carried out and applied in organizations to achieve organizational productivity. Many variables are affecting employee productivity, but in this study, researcher focused on motivational variable, which consist of intrinsic and ekstrinsic variabel. The purpose of this study was to determine how much influence intrinsic motivation and extrinsic motivation both partially and simultaneously on employee productivity. The research method used is a quantitative method by distributing questionnaires as a data collection tool. Based on the analysis, it was found that the variable intrinsic motivation (X1) and extrinsic motivation (X2) had a positive and significant effect on the variable employee productivity (Y) at PT Nanbu Plastics Indonesia